2009
DOI: 10.1016/j.jmb.2009.03.051
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Escherichia coli Polynucleotide Phosphorylase Core Bound to RNase E, RNA and Manganese: Implications for Catalytic Mechanism and RNA Degradosome Assembly

Abstract: Polynucleotide phosphorylase (PNPase) is a processive exoribonuclease that contributes to messenger RNA turnover and quality control of ribosomal RNA precursors in many bacterial species. In Escherichia coli, a proportion of the PNPase is recruited into a multi-enzyme assembly, known as the RNA degradosome, through an interaction with the scaffolding domain of the endoribonuclease RNase E. Here, we report crystal structures of E. coli PNPase complexed with the recognition site from RNase E and with manganese i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
167
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(175 citation statements)
references
References 60 publications
(88 reference statements)
6
167
0
Order By: Relevance
“…In E. coli, RNase E interacts with PNPase via a fragment of 23 residues (GAAGGHTAT HHASAAPARPQPVE, residues 1039-1061) (Callaghan et al 2004;Nurmohamed et al 2009), while in C. crescentus, the site is demonstrated to be the GWW motif (EKPRRGWW RR, residues 889-898) (Hardwick et al 2011(Hardwick et al , 2012. We showed that a highly conserved motif of cyanobacterial RNase E within the noncatalytic domain of AnaRne could bind to AnaPnp.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In E. coli, RNase E interacts with PNPase via a fragment of 23 residues (GAAGGHTAT HHASAAPARPQPVE, residues 1039-1061) (Callaghan et al 2004;Nurmohamed et al 2009), while in C. crescentus, the site is demonstrated to be the GWW motif (EKPRRGWW RR, residues 889-898) (Hardwick et al 2011(Hardwick et al , 2012. We showed that a highly conserved motif of cyanobacterial RNase E within the noncatalytic domain of AnaRne could bind to AnaPnp.…”
Section: Discussionmentioning
confidence: 88%
“…In terms of residue composition, these PNPase recognition sites display great variation. Accordingly, the regions on E. coli and C. crescentus PNPases that determine RNase E recognition are also distinct (Nurmohamed et al 2009;Hardwick et al 2012). These differences probably reflect the long coevolution history of PNPase-RNase E interactions in different species.…”
Section: Discussionmentioning
confidence: 99%
“…87,116 PNPase has been shown to be associated with endonuclease RNase E and other proteins in the RNA degradosome. [117][118][119] In vitro, PNPase catalyzes phosphorolytic degradation of RNA, releasing nucleoside ©2 0 1 1 L a n d e s B i o s c i e n c e .…”
Section: Discussionmentioning
confidence: 99%
“…PNPase and the truncated core of PNPase lacking the S1 and KH domains were purified as described (42). Ribonuclease R (RNR07250; Epicentre) was stored at −20°C.…”
Section: Methodsmentioning
confidence: 99%